Do comorbidities predict pain and function in knee osteoarthritis following an exercise intervention, and do they moderate the effect of exercise? Analyses of data from three randomized controlled trials. (14th December 2019) - Legha, Amardeep; Burke, Danielle L.; Foster, Nadine E.; van der Windt, Danielle A.; Quicke, Jonathan G.; Healey, Emma L.; Runhaar, Jos; Holden, Melanie A.
Abstract: Background: Although exercise is a core treatment for people with knee osteoarthritis (OA), it is currently unknown whether those with additional comorbidities respond differently to exercise than those without. We explored whether comorbidities predict pain and function following an exercise intervention in people with knee OA, and whether they moderate response to: exercise versus no exercise; and enhanced exercise versus usual exercise‐based care. Methods: We undertook analyses of existing data from three randomized controlled trials (RCTs): TOPIK ( n = 217), APEX ( n = 352) and Benefits of Effective Exercise for knee Pain (BEEP) ( n = 514). All three RCTs included: adults with knee pain attributable to OA; physiotherapy‐led exercise; data on six comorbidities (overweight/obesity, pain elsewhere, anxiety/depression, cardiac problems, diabetes mellitus and respiratory conditions); the outcomes of interest (six‐month Western Ontario and McMaster Universities Arthritis Index knee pain and function). Adjusted mixed models were fitted where data was available; otherwise linear regression models were used. Results: Obesity compared with underweight/normal body mass index was significantly associated with knee pain following exercise, as was the presence compared with absence of anxiety/depression. The presence of cardiac problems was significantly associated with the effect of enhanced versus usual exercise‐based care for knee function, indicating that enhanced exercise may be less effective for improving knee function in people with cardiac problems. Associations for all other potential prognostic factors and moderators were weak and not statistically significant. Conclusions: Obesity and anxiety/depression predicted pain and function outcomes in people offered an exercise intervention, but only the presence of cardiac problems might moderate the effect of exercise for knee OA. Further confirmatory investigations are required.